2015
DOI: 10.1007/s13277-015-4608-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of serum miRNAs by nano-quantum dots microarray as diagnostic biomarkers for early detection of non-small cell lung cancer

Abstract: Circulating microRNAs (miRNAs) are potential noninvasive biomarkers for cancer detection. We used preoperative serum samples from non-small cell lung cancer (NSCLC) patients and healthy controls to investigate whether serum levels of candidate miRNAs could be used as diagnostic biomarkers in patients with resectable NSCLC and whether they were associated with clinicopathologic characteristics. We initially detected expression of 12 miRNAs using quantitative reverse transcriptase polymerase chain reaction (qRT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 36 publications
3
66
1
Order By: Relevance
“…Abnormalities in miR-16 levels have been reported in various types of cancers, suggesting that miR-16 is involved in tumor formation and progression. The miRNA microarray analysis of lung cancer and adjacent normal lung tissues showed that miR-16 was downregulated in lung cancer tissues (16)(17)(18). miR-16 plays a different role in the proliferation of different types of tumor cells by regulating a variety of mRNA target genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormalities in miR-16 levels have been reported in various types of cancers, suggesting that miR-16 is involved in tumor formation and progression. The miRNA microarray analysis of lung cancer and adjacent normal lung tissues showed that miR-16 was downregulated in lung cancer tissues (16)(17)(18). miR-16 plays a different role in the proliferation of different types of tumor cells by regulating a variety of mRNA target genes.…”
Section: Discussionmentioning
confidence: 99%
“…miR-16 plays important roles in regulating the development of organisms and cell self-renewal, differentiation and many other physiological activities. The miRNA microarray analysis of lung cancer and adjacent normal lung tissues showed the miR-16 is downregulated in lung cancer tissues (16)(17)(18). miR-16 was found to be downregulated in lung squamous cell carcinomas and adenocarcinomas, which was correlated with the expression of cyclin D1 (19).…”
Section: Introductionmentioning
confidence: 99%
“…Fan and coworkers found five serum miRNAs (miR-16-5p, miR-17b-5p, miR-19-3p, miR-20a-5p, and miR-92-3p) that were significantly downregulated while miR-15b-5p was significantly upregulated in NSCLC [41]. Treatment procedures also affect the levels of circulating miRNA.…”
Section: Exosomes and Circulating Rnamentioning
confidence: 99%
“…Since circulating miRNAs were first identified in human plasma in 2008, a great many of studies have been aiming at identifying a reliable diagnostic tool by investigating the differential expression of circulating miRNAs between NSCLC patients and healthy controls or patients harboring benign tumors. For instance, Lihong Fan et al have demonstrated that a predictive model combining serum miR-15b-5p, miR-16-5p, miR-20a-5p can be used to discriminate the early stage of NSCLC cases from healthy subjects (Fan et al, 2015). Reassuringly, the fact that this study applied two different methods (RT-qPCR and Nano-quantum dots microarray) to identify the same differential expression of serum miRNAs, which may have improved the sensitivity and reproducibility of the results.…”
Section: Circulating Mirnas As Diagnostic Biomarkers Of Nsclcmentioning
confidence: 99%